A cellular automaton model for offshore evacuation risk assessment. (April 2017) - Grand Blanc, Michel; Carpignano, Andrea; Dulla, Sandra; Marolo, Stefano
A new approach to assess the risk associated with jetfire and poolfire accidents on an offshore oil facility using cellular automata is presented. This model simulates many accident scenarios, and the related evacuation processes, adopting a Monte Carlo approach in order to evaluate an average consequence and then a more realistic value of the risk associated with these accidents. The results of this new method are discussed and compared with the results obtained from a traditional approach over a real case study. The comparison shows that this new approach supplies lower risk-related results, still being conservative; besides, it can supply further information useful in the design phase.